The Analysis of Doctoral Theses in Chemistry Education Defended in the Czech Republic between Years 2003–2014 - Rusek, Martin (Scientia in educatione, 2016)
The analysis of dissertations in Chemistry education defended between 2003 and 2014 has been conducted within a larger project focused on dissertations in Science education. The project is an endeavour to support the position of Science education in the Czech Republic. There were 39 dissertations defended in the selected period. These theses have been analysed with respect to their thematic focus, school level, methods of data collection and the authors’ publication activity. The number of defended theses increases gradually. The theses are usually focused on grammar school Chemistry education, the most common topics are educational experiments, recently also information and communication technology in education. The paper also appeals for facilitating dissertation sharing and further doctoral studies support. Along with the conclusions of the Accreditation Committee mentioned in the text, the results may contribute to improving the quality of doctoral studies.